Cryptic Biodiversity in Two Closely Related Curcuma (Zingiberaceae) Species in Thailand Revealed by Molecular and Morphometric Analyses - Khumkratok, Sutthira; Boontiang, Kriangsuk; Chutichudet, Prasit; Pramual, Pairot (Agriculture and Natural Resources, 2015)
The genus Curcuma L. has several significant uses including in herbal medicine, as food and for decoration. However, the taxonomy of this genus has posed a challenge to traditional taxonomy due to the great morphological variation related to high levels of polyploidization and extensive hybridization. This study investigated the morphological and genetic differentiation between two closely related Curcuma species—Curcuma gracillima and C. parviflora—in Thailand. Principal components analysis of the 15 morphological characters revealed three morphological groups. Specimens of C. parviflora formed one group while those of C. gracillima separated into two groups. Genetic analysis based on matK and internal transcribed spacer (ITS) sequences revealed greater genetic diversity in C. gracillima corresponding with its high morphological variation. Phylogenetic study revealed that C. parviflora is monophyletic; while, C. gracillima is polyphyletic due to samples of this species forming two distinct clades consistent with two morphologically divergent groups. Comparisons of the efficiency for discriminating species indicated that ITS is more effective than the matK sequences with nearly perfect species identification (95%) compared to 58% for matK sequences. Therefore, the ITS sequences should be used as the barcoding sequences, at least for Curcuma species.